Nanodelivery of Natural Antioxidants: An Anti-aging Perspective - Vaiserman, Alexander; Koliada, Alexander; Zayachkivska, Alina; Lushchak, Oleh (Frontiers in Bioengineering and Biotechnology, 2020)
The aging process is known to be associated with heightened oxidative stress and related systemic inflammation. Therefore, antioxidant supplementation is regarded as a promising strategy to combat aging and associated pathological conditions. Food-grade antioxidants from plant-derived extracts are the most common ingredients of these supplements. Phyto-bioactive compounds such as curcumin, resveratrol, catechins, quercetin are among the most commonly applied natural compounds used as potential modulators of the free radical-induced cellular damages. The therapeutic potential of these compounds is, however, restricted by their low bioavailability related to poor solubility, stability and absorbance in gastrointestinal tract. Recently, novel nanotechnology-based systems were developed for therapeutic delivery of natural antioxidants with improved bioavailability and, consequently, efficacy in clinical practice. Such systems have provided many benefits in preclinical research over the conventional preparations, including superior solubility and stability, extended half-life, improved epithelium permeability and bioavailability, enhanced tissue targeting and minimized side effects. The present review summarizes recent developments in nanodelivery of natural antioxidants and its application to combat pathological conditions associated with oxidative stress.